Anti-inflamatório dexametasona: estudos de biodegradabilidade, toxicidade, ocorrência e degradação oxidativa avançada em efluente hospitalar - Arsand, Daniel Ricardo (2010)
The presence of drugs and active substances in the environment has been a concern in recent years. A range of these compounds have been found in water treated in sewage treatment effluents, surface waters and less frequently in groundwater worldwide. The dexamethasone (DEX), an anti-inflammatory similar to hydrocortisone, is the most potent anti-inflammatory from the glucocorticosteroids, both being used in human and veterinary medicine. However, its use is related to problems of various orders. Considering the values PEC (Predicted Environmental Concentration) calculated for the concentration of DEX in the hospital effluents PA-HUSM, it can be said that they exceed the tolerable limit value (OECD) for the emission of effluents to aquatic environments (10 ng L-1), requiring additional study of environmental risk assessment. The amounts of DEX administered in PA-HUSM in Uni-Klinikum Freiburg (Germany, section tumors treatment) and the total amount of DEX administered in Germany (for the year 2007) was compared. Studies of biodegradation of DEX base, DEX acetate and DEX phosphate were conducted in accordance with standard methodology for OECD: Closed Bottle Test (CBT), Manometric Respirometry Test (MRT) and Zahn-Wellens Test (ZWT). Luminescent bacteria (Vibrio fischeri) were used in toxicological tests for evaluation of the toxicity of the aqueous solutions of the three chemical forms of DEX (base, acetate and phosphate), of the solutions post-biodegradation tests and after treatment solutions by electrocoagulation (EC) and/or photocatalysis (FC). It was used advanced oxidation processes (EC and FC) to study the chemical degradation and/or adsorptive removal of DEX from aqueous solutions and samples of hospital sewage. The combination of EC and FC processes in the removal of DEX was also investigated. The optimization of experiments was done with factorial design with the aid of response surface methodology (RSM). To study the degradation of the organic load was developed a new methodology for the determination of COD in the effluent hospital using deconvolution technique applied to UV-spectrophotometry. Likewise, it has developed procedures for clean up and pre-concentration of DEX with the aid of solid phase extraction (SPE). Studies of ready-degradation and biodegradation in aqueous solution showed that the chemical forms of the studied anti-inflammatory DEX are not biodegradable in the environment. Under optimized conditions, the EC presented capacity to remove about 30% of DEX, both, in aqueous solution and in samples of hospital sewage, and the adsorption process showed the predominant removal effect of DEX. According to the factorial design (RSM) the applied current and the concentration of supporting electrolyte were the most significant factors in the process. In studies of photocatalytic degradation in aqueous solution followed by chromatographic determination (HPLC-DAD) occurs total disappearance of the DEX signal in the first minutes (4-5 min) of photocatalysis. However, taking the reduction of COD measured by nondispersive IR as a parameter for mineralization, it appears that there was only partial mineralization; DEX was degraded to photoproducts that do not absorb in the spectral range used (UV). Toxicological studies with the luminescent bacteria Vibrio fischeri showed that the chemical forms of DEX (base, acetate and phosphate) have no acute or chronic toxicity, as well as products of biodegradation, photodegradation or electrocoagulation. Despite the fact that DEX not presented acute or chronic toxicity, it is not biodegradable, and therefore must undergo removal from the hospital sewage before being released to the aquatic environment.